GUESS THE SCORE GAME APPLICATIONS USING VISUAL BASIC PROGRAMMING LANGUAGE RELEASE 6.0 - R. Jenar Kusbandono; Ristyawati, SKom., MMSI Ristyawati, SKom., MMSI (Jurnal Sistem Informasi, 2005)
Writing is about a computer game applications. In writing this game applications, theÂ author outlines a few things about Visual Basic programming language, gameprograms and matters related to computer game itself.In this writing, the author makes a Windows-based computer game using VisualBasic 6.0 Release